2019
DOI: 10.1007/s10798-019-09500-0
|View full text |Cite
|
Sign up to set email alerts
|

Technological knowledge in early childhood education: provision by staff of learning opportunities

Abstract: Developments in early childhood education (ECE) over the last two decades have for many countries meant a change towards a more subject-oriented pedagogy in which preschool staff are commissioned to teach technology to young children. This has been proved to be a challenge to the staff. Through analysis of activities at two preschool units, this study shows how technology education can be provided in ECE, and what kind of knowledgelearning by children can be facilitated in different activities and depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
(28 reference statements)
1
16
0
Order By: Relevance
“…Previous studies have showed that technology education is described with both broadness and depth by preschool staff on an aggregated level . Observations of the practice show the teaching sometimes reflects the broadness and depth previously described (Sundqvist, 2020), while sometimes it is shallow and focuses on natural science rather than technology (Benson & Treleven, 2011;Campbell, 2010) In addition, scrutiny of Swedish preschools found they did not provide a satisfactory technology education, regarding neither content nor teaching methods (Swedish Schools Inspectorate, 2012, 2017. Keeping in mind the results of this study are based on the staff's statements, and thus cannot claim the same authenticity as the observation studies mentioned above, this study shows diverse approaches to technology education, in part reflecting the results from previous research.…”
Section: Diverse Descriptions Of Technology Educationmentioning
confidence: 73%
See 2 more Smart Citations
“…Previous studies have showed that technology education is described with both broadness and depth by preschool staff on an aggregated level . Observations of the practice show the teaching sometimes reflects the broadness and depth previously described (Sundqvist, 2020), while sometimes it is shallow and focuses on natural science rather than technology (Benson & Treleven, 2011;Campbell, 2010) In addition, scrutiny of Swedish preschools found they did not provide a satisfactory technology education, regarding neither content nor teaching methods (Swedish Schools Inspectorate, 2012, 2017. Keeping in mind the results of this study are based on the staff's statements, and thus cannot claim the same authenticity as the observation studies mentioned above, this study shows diverse approaches to technology education, in part reflecting the results from previous research.…”
Section: Diverse Descriptions Of Technology Educationmentioning
confidence: 73%
“…Regarding the technological content, Sundqvist (2020) studied the opportunities given to children at two preschools. For the analysis, she used a framework developed in previous work on what preschool staff perceive as relevant content for technology education.…”
Section: Previous Research and Scrutiny On How Staff Teach And Perceive Technology Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire does not borrow questions from another instrument and was developed in accordance with steps for developing items in measurement and evaluation tools [78]. A literature review was conducted in order to establish validity by deriving from recent studies in the same field [5,24,25,[79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. In addition, informal meetings were carried out with preschool teachers who have preschool children of their own, in order to consult their evaluations regarding digital parenting.…”
Section: Digital Parenting Questionnairementioning
confidence: 99%
“…There are very diverse benefits of high quality ECEC services: social, economic and educational. In setting the groundwork for better skills for future EU people, ECEC services play a crucial role in enabling us to face the mid-and long-term challenges and to build a more trained workforce capable of responding to and adapting to technological change (Sundqvist, 2020). There is ample evidence that admission to high-quality ECEC systems results in far improved outcomes for international core competency assessments, such as PISA and PIRLS, which are equal to success in one or two academic years (Zhao, 2020).…”
Section: Introductionmentioning
confidence: 99%